Improving the EFL Students’ Oral Communication through the Implementation of Business Meetings Project Using a Digital Pocket Presentation Guide - Lia Agustina; Farida Ulfa; Futuh Handoyo (Association of Language Teachers in Southeast Asia (ALTSA), 2023)
This study aimed to implement a Business Meetings Project using a Digital Pocket Presentation Guide to improve EFL students' oral communication. Therefore, the action research design was implemented to match the purpose of the study. The data collection techniques were started by asking students to do a pretest, implement the model, do observations during the activities, distribute a questionnaire and do interviews to see the students' improvement by asking students to do the post-test. The result of the research showed that the student's progress sustainably improved from the first evaluation, which was 48,75, to the second evaluation, which was 53,760 and to the third evaluation, which was 56,25 for the mean. The score continuously improved from the first evaluation to the third evaluation. The results of the research show that the students gave good attitudes and responses during the process of implementing the model. Questionnaire and interview reports show that students agreed on the implemented model as it motivated and improved their self-confidence and capability in oral communication skills. In conclusion, implementing the business meeting projects through a digital pocket presentation guide enhanced students' verbal communication skills.